Odd and the Frost Giants - Gaiman, Neil (Harper, 2009)
An unlucky twelve-year-old Norwegian boy named Odd leads the Norse gods Loki, Thor, and Odin in an attempt to outwit evil Frost Giants who have taken over Asgard.